SIGS-S Mobile Saúde – A Mobile Application to Support the Collection of Health Data - Fernandes, Eduardo; Turine, Marcelo; Cagnin, Maria (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de Informação, 2015)
The Brazilian government has asked for information systems to support government activities such as health care. Aiming to support the collection of health data in the context of the Health in The Family Program (Programa Saúde na Família) promoted by the Single Health System of Mato Grosso do Sul (Sistema Único de Saúde do Estado de Mato Grosso do Sul – SUS-MS), it was developed the mobile application SIGS-S Mobile Saúde. The purpose of the mobile application is to provide the collection of health data in places where there is no internet connection using mobile devices such as tablets, providing the collected data to a web system called SIGS-S Web Saúde via internet data transfer. A software process, named ProFap, was used to support the mobile application development. As a result, the mobile application was developed and its documentation was prepared to help future software maintenance and the deployment of SIGS-S Mobile Saúde in the context of health care by SUS-MS. The application was developed and validated with participation of stakeholders consisting of health users and Brazilian government managers.